Evaluation of the Effective Temperature of Sunspots Using Molecular Parameters of AlF - K. Balachandrakumar; V. Raja; B. Karthikeyan; S. P. Bagare; N. Rajamanickam (Advances in Astronomy)
The physical conditions of celestial objects can be analyzed using the spectrum of atoms or molecules present in the object. The present work focuses on the spectroscopic analysis of astrophysically significant molecule AlF. The evaluation of Franck-Condon (FC) factors and r-centroids is done by a numerical integration procedure using the suitable potential energy curves for C1Σ+-A1Σ+, b3Σ+-a3Πr, c3Σ-a3Πr, and f3Π-a3Πr band systems of AlF molecule. The intensity of various bands is discussed with the help of derived FC factors. The band degradation and the nature of potential energy curves are studied using r-centroid values. The vibrational temperature of sunspot is estimated to be around 1220 ± 130 K which falls in the reported temperature range of cold sunspots.